Perceptions of Bedside Cardiac Critical Care Registered Nurses on 24 Hour Attending Intensivist Coverage. (6th June 2016) - Alfares, Fahad A.; Jones, Melissa B.; Ramakrishnan, Karthik; Endicott, Kendal M.; Zurakowski, David; Shankar, Venkat; Nath, Dilip S.
ABSTRACT: Objective: To elicit the perceptions of bedside critical care nurses toward continual in‐house attending coverage and its effect on patient safety, communication, and nursing education. Design: A 5‐point Likert‐type questionnaire was designed to evaluate the perception of bedside nurses in the pediatric cardiac intensive care unit (PCICU) toward the presence of a 24 hour in‐house attending physician. Setting: Single tertiary referral PCICU in Washington, DC Subjects: The 46 PCICU nurses who participated in the study were separated into two groups based on exposure to the recent implementation of continual in‐house attending coverage at our institution. Group one consisted of 14 nurses with only exposure to the new 24/7 in‐house coverage while group two encompassed 32 nurses who had experienced both the new and old system (off‐site on‐demand attending physician). Measurements and Main Results . Surveys demonstrated that both groups found that the new system has a positive impact on nursing education (median score of 5) as well as a positive impact on the communication between multidisciplinary teams and between care team and families (median score of 5). Nurses who experienced only the new system scored one point lower (median score of 4) regarding the effect of this staffing model on patient outcomes than nurses who had experienced both systems (median score of 5, P  = .016). Between 83% and 98% of all 46 nurses who participated indicated they agree or strongly agree with each of the questions regarding the benefit of 24 hour in‐house attending coverage. Conclusion: Our study suggests that regardless of differences in experience, pediatric cardiac nurses believe the presence of an on‐site intensivist to be beneficial to both nursing and patients.